Comparison of two percutaneous pinning methods for the treatment of the pediatric type III supracondylar humerus fractures - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
Fifty-nine surgically treated cases of type III supracondylar humeral fractures were retrospectively evaluated. Fracture fixation was performed by either crossed K-wires in 35 patients (group I) or lateral K-wires in 24 patients (group II). The reoperation rates and neural injury rates as major complications were similar in the two groups and all neural injuries except one had full recovery. At the last follow-up exam six patients in group I (17%) and four patients in the group II (116%) had apparent cosmetic deformities. No major differences were found between the results of each group. In order to reduce complications an experienced supervision is necessary during surgery of these seemingly benign fractures. (C) 2003 Lippincott Williams Wilkins.
Keywords: supracondylar humerus fracture; percutaneous pinning; CLOSED REDUCTION; CHILDREN; FIXATION; PREVENTION; DEFORMITY; TRACTION